Tabung Haji's global standards for hajj management - Raja Yusof, Raja Nerina; Zawawi, Dahlia (Universiti Putra Malaysia Press, 2014)
This case is about Lembaga Tabung Haji Malaysia (TH) and its uniqueness as the first and only model of a dedicated institution in the world to systematically manage the Hajj pilgrimage. Since performing Hajj is one of the pillars in Islam, there is an increasing number of Muslims who want and are able to perform Hajj, hence the need for a systematic method of managing the whole journey. TH was established to do just that; and the institution has managed to perform effectively and efficiently throughout the years. This case study highlights among others, the role of Tabung Haji Act, TH investment and savings plans for pilgrims-to-be, and TH Staff to be among the many unique characteristics that have given the institution global recognition for hajj management.